Analysis Of The Kampung Batu Malakasari Baleendah Swimming Pool In Bandung On Sustainable Tourism And Its Impact On The Community - Arba, Arsya; Ramdani, Dadan (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the contribution of the Kampung Batu Malakasari Swimming Pool, located in Baleendah, Bandung, to the development of sustainable tourism and its impact on the local community. The research method used was qualitative, with data collection techniques including interviews, observation, and documentation. The results indicate that the presence of Kampung Batu Malakasari has had positive impacts socially, economically, and environmentally. The surrounding community experienced direct benefits in the form of job creation, increased income, and business opportunities through the MSME sector. Meanwhile, tourists expressed satisfaction with the friendly service, diverse attractions, and clean and well-maintained environment. Although official data on budget allocation is not yet available, the analysis indicates that the development of infrastructure, public facilities, and sanitation systems at the tourist site reflects sound management and supports sustainability principles. This study recommends strengthening budget planning and community involvement in tourism development to ensure long-term benefits.